Effectiveness of Endophytic Bacterial Consortium of Coffee Plant on Mortality of Pratylenchus Coffeae in Vitro - dwi halimah; Abdul Munif; Giyanto Giyanto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2015)
Bacteria live in wild in form of a consortium. Use of microbial consortium tends to give better results than single isolate, because the action of enzyme of each type of microbe can complement each other in order to survive. This study aimed to study the effectiveness of bacterial endophytic consortium from coffee plant on plant growth and mortality of parasitic nematodes in coffee. Isolation of bacteria is conducted  by growing the crushed roots, stems and leaves of coffee on 20% TSA media, then testing their hemolysis and hypersensitivity reaction. Selected isolates were tested on their effect on the growth of seedling and Pratylenchus coffeae mortality, as well as their chitinolytic, proteolytic, lipolytic, HCN production, dissolution of phosphate (P) and fixation of nitrogen (N2) abilities. The results showed that from 27 isolates of the consortium, 23 isolates showed negative reaction to hypersensitive test and 9 isolates to hemolysis test. The highest mortality rate was shown by K6 isolate (65.8%). The highest growth was shown by K15 and K 21 isolates while the highest root length by K21 isolate. Further analisys showed that 100% of the isolates could hydrolyze proteases, lipid, and produce HCN, while chitinolytic activity was shown by 78% isolates which could fix N2 and 11% of isolates could dissolve phosphate.